2008
DOI: 10.2337/db07-1214
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 Protects β-Cells From Interleukin-1β–Induced Apoptosis by Interfering With the c-Jun NH2-Terminal Kinase Pathway

Abstract: OBJECTIVE— The pro-inflammatory cytokine interleukin-1β (IL-1β) generates pancreatic β-cells apoptosis mainly through activation of the c-Jun NH2-terminal kinase (JNK) pathway. This study was designed to investigate whether the long-acting agonist of the hormone glucagon-like peptide 1 (GLP-1) receptor exendin-4 (ex-4), which mediates protective effects against cytokine-induced β-cell apoptosis, could interfere with the JNK pathway. RESEARCH DESIGN AND METHODS— Isolated human, rat, and mouse isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
114
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 53 publications
(61 reference statements)
7
114
0
Order By: Relevance
“…Signalling mechanisms involved in exendin-4 inhibition of palmitate-mediated apoptosis IB1, a scaffold protein that tethers components of the JNK pathway acting as an endogenous blocker, has been suggested to mediate the protective actions of exendin-4 against apoptosis elicited by the cytokine, IL-1β [19]. Therefore, IB1 was next studied in the context of exendin-4 inhibition of NEFA-induced apoptosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Signalling mechanisms involved in exendin-4 inhibition of palmitate-mediated apoptosis IB1, a scaffold protein that tethers components of the JNK pathway acting as an endogenous blocker, has been suggested to mediate the protective actions of exendin-4 against apoptosis elicited by the cytokine, IL-1β [19]. Therefore, IB1 was next studied in the context of exendin-4 inhibition of NEFA-induced apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…GLP-1 receptor agonists can inhibit the proapoptotic pathways triggered by a variety of stimuli, including IL-1β, TNF-α and rapamycin, by interfering with JNK and possibly p38 MAPK activation [15,19,46]. The cAMP/PKA/CREB cascade represents a central mechanism of GLP-1 action, specifically when this relates to promotion of beta cell survival [47], even though other signalling mediators may also be implicated [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…GLP-1RAs have protective effects on cytokine-induced apoptosis in beta cells by interfering with the JNK pathway. Exendin-4 also protects beta cells from interleukin-1 beta-induced apoptosis by interfering with the JNK pathway [77] . Zhang et al [78] treated mice on a high-fat diet with 1 mg/kg liraglutide twice a day, and after 8 wk, the results showed that JNK phosphorylation was significantly reduced.…”
Section: Glp-1ras and Inflammatory Signal Transduction Pathwaysmentioning
confidence: 99%
“…However, the effects of immunomodulatory treatments are not limited to tissues involved in disease pathophysiology and thus might have unwarranted side effects. Moreover, current antidiabetes drugs may alleviate systemic and tissue-specific inflammation (4)(5)(6)(7)(8)(9)(10)(11)(12), and therefore the added value of using specific immunomodulatory treatments needs to be confirmed. Herein, we review the anti-inflammatory and metabolic effects of standard antidiabetes medications and of novel anti-inflammatory treatments.…”
mentioning
confidence: 99%